2015
DOI: 10.1016/j.ijgo.2015.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node micrometastases in initial stage cervical cancer and tumoral recurrence

Abstract: The presence of lymph node micrometastases is an important risk factor for tumor recurrence. These patients should be considered eligible for adjuvant radiochemotherapy treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 22 publications
1
36
1
1
Order By: Relevance
“…Studies have shown that over the past three decades, SCC of the cervix has been progressively decreasing in proportion to the increase of adenocarcinoma, also found in our study [13][14][15][16][17]. However, in a more current reality, this can be explained due to the better public access to the examination of cervical cytological screen- ing.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Studies have shown that over the past three decades, SCC of the cervix has been progressively decreasing in proportion to the increase of adenocarcinoma, also found in our study [13][14][15][16][17]. However, in a more current reality, this can be explained due to the better public access to the examination of cervical cytological screen- ing.…”
Section: Discussionsupporting
confidence: 66%
“…This examination has better effectiveness in identifying intraepithelial neoplasias and precursors of SCC in relation to precursors of adenocarcinomas. Positive pelvic lymph node is one of the most important prognostic factors in cervical cancer [4,[7][8][9]13,18,19]. Increased rates of lymph node metastasis in the comparison of the two historical series maintained a close relationship with the concomitant growth of adenocarcinoma type.…”
Section: Discussionmentioning
confidence: 99%
“…Zaal et al [27] analyzed the same study cohort and claimed that overall survival was significantly better if more than 16 nonSLNs were removed in patients with SLN micrometastases or isolated tumor cells. In addition, micrometastasis was a reported risk factor for tumor recurrence according to a multivariate regression analysis by Colturato et al [28]. Tax et al [29] searched PubMed, Embase, CINAHL, and the Cochrane database to assess the clinical significance of ultrastaging of lymph nodes and claimed that early-stage cervical cancer patients who had no suspicious pre-or perioperative lymph nodes and who had bilateral negative SLNs after ultrastaging had a residual risk of below 0.1% of occult metastases.…”
Section: Discussionmentioning
confidence: 99%
“…17 Although prospective data are lacking, retrospective studies have suggested that micrometastasis is an independent poor prognostic factor for overall survival. [18][19][20][21] In our model, the presence of micrometastasis was treated as a high-risk criterion, and these patients were treated with adjuvant chemoradiation. There is little evidence about the prognostic significance and management of isolated tumor cells, and as such, these patients were managed as node-negative in our model.…”
Section: Decision Modelmentioning
confidence: 99%